Vehicular safety using Medium Access Control and Particle Swarm Optimization - Choudhary, Shilpa; Kaushik, Awanish; Vats, Mudita; Mishra, Arpana (International Journal of Engineering and Technology, 2018)
Vehicular ad hoc networks (VANET) are emerging as a prominent form of mobile ad hoc networks (MANETs) and as an effective technology for providing a wide range of safety applications for vehicle passengers. Nowadays, VANETs are of an increasing importance as they enable accessing a large variety of ubiquitous services. Such increase is also associated with a similar increase in vulnerabilities in these inter-vehicular services and communications, and consequently, the number of security attacks and threats. It is of paramount importance to ensure VANETs security as their deployment in the future must not compromise the safety and privacy of their users. The successful defending against such VANETs attacks prerequisite deploying efficient and reliable security solutions and services, and the research in this field is still immature and is continuously and rapidly growing. As such, this paper is devoted to provide a structured and comprehensive overview of the recent research advances on VANETS nodes crossing each other but having no collision between them using mac protocol a layer of data link layer and particleÂ swamp optimization technique (PSO) that is a probabilistic approach to send a best probable massage to the link layer or mac protocol , and we are also using theÂ frequency range of 5.9GHZ of dedicated short range communication (DSRC) a family of IEEE 108.11ac.Â